Lung Ultrasound Score as a Predictor of Failure to Wean COVID-19 Elderly Patients off Mechanical Ventilation: A Prospective Observational Study - Wang Y; Yi Y; Zhang F; Yao YY; Chen YX; Wu CM; Wang RY; Yan M (Clinical Interventions in Aging, 2024)
Ying Wang,1,* Yu Yi,1,* Fan Zhang,1 Yuan-Yuan Yao,2 Yue-Xiu Chen,2 Chao-Min Wu,2 Rui-Yu Wang,2 Min Yan1,2 1Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, 221004, People’s Republic of China; 2Department of Anesthesiology, the Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, 310016, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Yan, Email zryanmin@zju.edu.cnBackground: The lung ultrasound score was developed for rapidly assessing the extent of lung ventilation, and it can predict failure to wean various types of patients off mechanical ventilation. Whether it is also effective for COVID-19 patients is unclear.Methods: This single-center, prospective, observational study was conducted to assess the ability of the 12-region lung ultrasound score to predict failure to wean COVID-19 patients off ventilation. In parallel, we assessed whether right hemidiaphragmatic excursion or previously published predictors of weaning failure can apply to these patients. Predictive ability was assessed in terms of the area under the receiver operating characteristic curve (AUC).Results: The mean age of the 35 patients in the study was (75 ± 9) years and 12 patients (37%) could not be weaned off mechanical ventilation. The lung ultrasound score predicted these failures with an AUC of 0.885 (95% CI 0.770– 0.999, p < 0.001), and a threshold score of 10 provided specificity of 72.7% and sensitivity of 92.3%. AUCs were lower for previously published predictors of weaning failure, and right hemidiaphragmatic excursion did not differ significantly between the two groups.Conclusion: The lung ultrasound score can accurately predict failure to wean critically ill COVID-19 patients off mechanical ventilation, whereas assessment of right hemidiaphragmatic excursion does not appear helpful in this regard.Trial Registration: https://clinicaltrials.gov/ct2/show/NCT05706441.Keywords: lung ultrasound score, diaphragmatic excursion, spontaneous breathing trial, weaning, COVID-19, critical care